Legal Risks and International Regulatory Pathways of Prepaid Fund Supervision in the Era of Artificial Intelligence - Zhang, Yi (Technium Social Sciences Journal, 2025)
The application of artificial intelligence technology in the field of prepaid business has disrupted the existing regulatory mode and process. Although several countries have basically formed relatively mature legal norms in the supervision of prepaid funds, they still face many problems and challenges in the international cooperation in the field of transnational prepaid funds. First, the regulatory rules are fragmented, cross-border supervision lacks a unified coordination mechanism, and the application of AI technology further exacerbates the failure of cross sectoral cooperation; Second, the abuse of technology has led to cross-border compliance arbitrage, highlighting the risks of algorithm manipulation and discrimination, and the lack of international cooperation has led to the exploitation of regulatory loopholes; Third, differences in national regulatory rules restrict international mutual recognition, and differences exist in the form of capital isolation and AI governance standards, which hinder the development of cross-border prepayment business. Collaborative governance should be strengthened, and international organizations should take the lead in formulating the basic principles and guidelines for the supervision of international prepaid funds to unify the core standards; Besides, we should also standardize the application of AI, clarify the technical bottom line standards, establish a cross-border regulatory cooperation platform, and strengthen information sharing and implementation linkage; Finally, we should implement hierarchical supervision, refine operators' filing standards, information disclosure obligations and risk prevention and control requirements, and strengthen access and compliance management.